Correlation of Students’ Reading Comprehension and Geometry Thinking Levels - Ursulasari, Yuan; Susanto,; Sunardi,; Nahrowi, (International Journal of Scientific Research and Management (IJSRM), 2019)
In Mathematic, student’s reading comprehension ability can be seen in their ability to change contextual Math problems into Math models. The ability of student changing a text which contain Math problems into Math models must have connection with their ability in understanding geometry problems. Considering that rigor level, the highest level of geometry thinking ability, a deep understanding and high rigor for student to understand the text. There must be a correlation between students’ reading comprehension ability and geometry thinking levels. The subjects of this research are 31 students of 10th grade in science class. They were given van Hiele Test to check their geometry thinking levels. The result of this research shows that the result of students’ thinking level test and reading comprehension test has 0.466 as coefficient of correlation which means that there is a positive correlation between both abilities, the correlation is not strong.